The Excitation System of 727.5 MVA Synchronous Generator of the Unit B1 in TPP "Nikola Tesla B" - Joksimović, Dušan; Ćirić, Zoran; Stojić, Đorđe M.; Arnautović, Dušan; Milinković, Milan; Veinović, Slavko; Milojčić, Nemanja (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
This paper presents a technical solution for the replacement of the excitation system of the unit B1 in TPP "Nikola Tesla B" as a part of the maintenance service in 2012. Since the generators of TPP "Nikola Tesla B" have the greatest power in the power system of Serbia, it was necessary to achieve high reliability in the excitation system so that the process of producing electricity is not endangered Considering this, the implemented excitation system uses modern technology with redundancy both in the power and control blocks, which resulted in an increase in the hot reserve by 100%. In addition, it was necessary to adjust the excitation system to the increased generator power and performance from 618MW to 667.5MW. In this paper, the main parameters of the excitation system are given: the power, the excitation system control, the thyristor ignition system, the event recorder system, the digital relay protection, as well as the measuring and signalling functions.